A COMPREHENSIVE ANALYSIS OF FINANCIAL LITERACY AND ITS CONTRIBUTION TO SUSTAINABLE FINANCIAL PRACTICES AMONG RURAL STUDENTS IN DISTRICTS OF HIMACHAL PRADESH - Sharma, Charu Arora; Sondhi, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study looks at financial literacy levels among rural higher education students in districts of Himachal Pradesh, India. As financial literacy becomes increasingly essential in navigating complex economic environments, understanding its role in shaping sustainable financial behaviors is crucial. The research investigates the current state of financial knowledge among rural students, focusing on their abilities in budgeting, saving, investing, and managing financial risks. Utilizing a mixed-method approach, data were collected from students aged 18–23 from diverse academic backgrounds through structured questionnaires and in-depth interviews. The findings reveal significant disparities in financial literacy levels across different districts, influenced by socio-economic factors, access to financial educationThe study uses a sample of 520 students aged 18-25 from diverse academic disciplines to investigate the relationship between financial literacy and environmental sustainability awareness. The study used a structured questionnaire methodology to collect data on demographics, educational background, and attitudes towards financial literacy efforts. While 58.1% of students exhibit an interest in learning about financial-environmental linkages, standard financial management programs are met with significant skepticism (54.8%). The results show a gender distribution of 54.8% female and 45.2% male respondents, with the majority (42.5%) being second-year students. Parental literacy levels are moderate, with 34.2% of fathers and 33.8% of mothers completing secondary education.The study found that 80.6% of students rely primarily on parental support for their education financing. The findings reveal significant disparities in financial literacy levels across different districts and suggest a complex relationship between financial literacy, environmental sustainability awareness, and educational background in rural higher education settings.